Longer storage duration of red blood cells is associated with an increased risk of acute lung injury in patients with sepsis - Janz, David R (Springer, 2013)
BACKGROUND: The storage duration of red blood cells transfused to critically ill patients is associated with increased morbidity and mortality. Whether the association exists between storage duration of red blood cells transfused to patients with sepsis and the risk of developing ALI/ARDS is unknown. We aimed to determine the association of the storage duration of red blood cells transfused to patients with sepsis and risk of developing acute lung injury in the subsequent 96 hours, with comparator trauma and nonsepsis/nontrauma groups. METHODS: We conducted a retrospective observational study of 96 transfused, critically ill patients with sepsis, 176 transfused, critically ill patients with traumatic injury, and 125 transfused, critically ill nontrauma, nonsepsis patients. The primary outcome was the development of ALI/ARDS up to 96 hours after transfusion. RESULTS: In 96 patients with sepsis, 49 (51%) patients developed ALI/ARDS. The median storage duration of transfused blood in the ALI/ARDS group was greater (24.5 days, interquartile range (IQR) 20–31) compared with the patients who did not develop ALI/ARDS (21 days, IQR 15–27, p = 0.018). Longer median storage duration was independently associated with an increased risk of developing ALI/ARDS in the subsequent 4 days (odds ratio 1.8, p = 0.028). The same association was not seen in the trauma or nonsepsis, nontrauma patients. CONCLUSIONS: Transfusion of blood with longer median storage duration to patients with sepsis is associated with a higher risk of developing ALI up to 4 days after transfusion. This same association is not seen in other critically ill patient populations.